PENGEMBANGAN WEBQUEST BERBASIS INKUIRI PADA MATA KULIAH ASESSMEN PEMBELAJARAN DI STKIP PGRI LAMONGAN - Ety Youhanita (FKIP Unirow Tuban, 2018)
This study aims to determine the development of the mindset of learners who often receive the material in the form of problem solving. This type of research using research development, the subject of research is the students of economic education. Data collection tool in the form of documentation and questionnaire using Likert scale. The research results show on the webquest development process in 3 stages. The initial stage of development is the learner is required to analyze and manage the learning outcomes by developing the instrument to be evaluated, the inquiry-based webquest method directs the learners to browse and is able to solve the existing case study at webquest stage. The second stage of development by using the development model of Peter Fenrich is developing CRT where CRT is developed with a questionnaire as a media feasibility tool webquest consists of 20 items of question, then develop a learning strategy that is using the first principle of introduction learning, task, process, evalution and last conclusion. The last stage is evaluation with trial review on some experts, among others media experts who stated media developed with a score of 70.5%, material experts said the media got a value of 72% while the individual test media developed a score of 77.5 %. The development of webquest media based on inquiry has fulfilled the purpose of developing webquest skills of learners starting there is a more complex increase.